Lost tribe of the Sith : the collected stories - Miller, John Jackson (Del Rey, 2012)
"At last in one volume, the eight original installments of the epic ... eBook series, along with the explosive, never-before-published finale, 'Pandemonium,' -- more than one hundred pages of new material!"--P. [4] of cover.